Strategi Bertahan UMKM dalam Menghadapi Perubahan Ekonomi Digital: Studi Kasus di Lingkungan Lokal - Ciek Julyati Hisyam; Nayla Agusta Wibowo; Kiranti Bening Penta Delima; Philia Zefanya; Farah Nursalimah; Defrisza Shandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of the digital economy has transformed business models and consumer behaviour, thereby prompting Micro, Small and Medium-sized Enterprises (MSMEs) to adapt in order to ensure the sustainability of their businesses. This study aims to analyse the survival strategies employed by MSMEs in the face of the digital economy’s development, as well as to identify the factors that support and hinder the adaptation process. The research employs a qualitative approach using the case study method. Data were obtained through in-depth interviews with two MSME operators in the vicinity of Jakarta State University and supported by a literature review. Data analysis utilised Talcott Parsons’ Theory of Adaptation, William F. Ogburn’s Theory of Social Change, and Max Weber’s Theory of Social Action. The results indicate that MSME operators utilise social media as a promotional tool and QRIS as a digital payment method to support their business activities. The utilisation of these technologies facilitates transactions, improves service quality, and expands market reach. However, the adaptation process still faces obstacles in the form of limited digital literacy, internet connectivity issues, and sub-optimal technological skills. Furthermore, good service, communication with customers, and the ability to build consumer loyalty are key factors in sustaining the business. This study concludes that the combined use of digital technology and high-quality service is a key strategy for MSMEs to survive and thrive in the digital economy.